Reporte del tamaño de una camada de barisia imbricata (wiegmann, 1828) (reptilia: anguidae) - Aguilar-Martínez, Gustavo F. (Instituto de Ecología, A.C., 2011)
The genus Barisia is endemic to Mexico occurring in temperate regions, at elevations between 2200-3800 m above sea level. Few records of clutch size of the species of Barisia are available, in particular for B. imbricata. The first report of a large clutch size (15 neonates alive) is given for this species.